2008
DOI: 10.1007/s00384-007-0409-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with carcinoma of the right colon invading the duodenum or pancreatic head

Abstract: Morbidity and mortality after colectomy and en bloc partial duodenectomy or pancreaticoduodenectomy are high but in selected cases could offer prolonged survival. Aggressive surgery including major resection should be performed to obtain clear resection margins even in case of complicated forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 19 publications
3
48
1
10
Order By: Relevance
“…10,[17][18][19] Kapoor et al 9 described two patients out of six who returned to the OR. Fuks et al 6 described two patients that required return to the OR. Their study reported 3 pancreaticoduodenectomy patients and 12 lateral duodenectomy patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…10,[17][18][19] Kapoor et al 9 described two patients out of six who returned to the OR. Fuks et al 6 described two patients that required return to the OR. Their study reported 3 pancreaticoduodenectomy patients and 12 lateral duodenectomy patients.…”
Section: Discussionmentioning
confidence: 98%
“…In up to 60-100% of the cases, adhesions between the tumor and adjacent structures are found to represent direct invasion upon histologic review. [6][7][8][9][10] If these principles are not followed, the consequences are notable. Early local recurrence rates of 70-100% are seen in patients who undergo separation of adjacent organs rather than en bloc resection.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We searched the medical literature using PubMed with the key words "duodenocolic fistula" from 1997 through 2012 and identified a total of 20 cases (2, 6-24). The etiology was benign in 10 cases (Crohn's disease (CD), 4 (6-9); foreign body ingestion, 1 (10); ulcerative colitis, 1 (11); duodenal ulcer, 1 (12); tuberculosis, 1 (13); abscess cavity, 1 (14); stent migration, 1 (15)) and malignant in 10 cases (colon cancer, 8 (2,(16)(17)(18)(19)(20)(21)(22); lymph node metastasis from colon cancer, 2 (23,24)). The frequencies of the causal factors in the 136 cases of benign DCF, including our case, are listed in Table 2.…”
Section: Discussionmentioning
confidence: 99%